REIMAGINING WOMANHOOD: THE INTERSECTION OF INDIC TRADITIONS AND FEMINIST CONSCIOUSNESS IN THE POETRY OF INDIAN ENGLISH WOMEN POETS - Vatsala; Kamboj, Kiran; Pant, Girish (ShodhKosh: Journal of Visual and Performing Arts, 2024)
The poetry of Indian English women poets serves as a powerful medium for expressing the evolving notions of womanhood, negotiating between Indic traditions and contemporary feminist consciousness. Rooted in the cultural ethos of mythology, spirituality, and heritage, these poets engage with traditional frameworks while challenging patriarchal structures through their verse. Their works reflect a deep engagement with gender identity, social resistance, and self-expression, offering a nuanced critique of both indigenous and global feminist movements. The interplay between modernity and tradition in their poetry highlights the ongoing struggle for agency and empowerment, as they reclaim narratives that have historically marginalized women’s voices. Through a blend of personal experience, collective memory, and literary innovation, Indian English women poets reimagine femininity, asserting their place in the larger discourse of gender and literary studies. The present paper is an honest attempt to attract readers’ attention to Reimagining Womanhood: The Intersection of Indic Traditions and Feminist Consciousness in the Poetry of Indian English Women Poets. The research scholar further writes that their poetic expressions transcend geographical boundaries, contributing to the global feminist literary canon while remaining deeply rooted in the socio-cultural realities of India.